Cooperative Script Method: A Study of to Improve Secondary Students’ Reading Comprehension on Descriptive Text - Hartanti, Rezkiah; Rahman, Agus; Rosiana, Rosiana; Saputra, Dian (JULIET: Journal of English Language and Literature, 2024)
This research was conducted to find out whether the use of cooperative script method improve students’ reading comprehension on descriptive text. The researcher used quantitative method with the design was quasi experimental exactly nonequivalent design with two group pre-test post-test design. The population of this research was taken at 249 students in the second grade of Madrasah Tsanawiyah Negeri Model Kota Sorong and the sample of this research was Class VIII C and VIII E that each class consist of 30 students. There was significant difference between pretest and posttest in experimental group and control group. The result showed that the mean score post-test of experimental group (88.8) was higher than the mean score post-test of control group (57). To compare the two result between experimental and control group, the researcher used t-test formula and the result of t-test formula was 8,33572. By using the degree of significance 5% or 0.05 in the table it was obtained 2,0017. Thus, alternative hypothesis (H1: 8,33572> 2,0017) was accepted because t-test value was higher than t table value. Therefore, the researcher concluded that cooperative script method can improve students’ reading comprehension on descriptive text.